Meeting the MDG drinking water and sanitation target : the urban and rural challenge of the decade (WHO GenevaCH, 2006)
Analyzes how access to drinking water and sanitation services is evolving, looks into the trends in urban and rural areas and how these are related to the likelihood of achieving the MDG drinking water and sanitation target. Compares projected coverage in 2015, based on the 1990-2004 trend, with the MDG drinking water and sanitation target.
Keywords: WATER RESOURCES